Early wound morbidity and clinical outcomes associated with P4HB mesh compared to permanent synthetic mesh in umbilical and small to medium, routine ventral hernia repairs - Deeken, Corey R.; Rosen, Michael J.; Poulose, Benjamin K.; Bradbury, Kasia; Huang, Li-Ching; Ma, Jianing; Badhwar, Amit (Frontiers in Surgery, 2023)
Permanent synthetic meshes such as polypropylene (PP) have been utilized for hernia repair for decades, but concerns remain regarding potential long-term, mesh-related complications. A resorbable polymer such as poly-4-hydroxybutyrate (P4HB) represents an alternative with high initial strength, that gradually resorbs, leaving an abdominal wall that is at least as strong as it would be in its native state. We aimed to compare early wound morbidity and clinical outcomes associated with P4HB to traditional, permanent PP in umbilical and small to medium, routine ventral hernias using data from the Abdominal Core Health Quality Collaborative (ACHQC).Inclusion criteria for the umbilical cohort included: all Centers for Disease Control and Prevention (CDC) wound classes, all Ventral Hernia Working Group (VHWG) hernia grades, and hernia defects < 3cm. The small to medium, routine ventral hernia cohort was limited to CDC class I wounds, VHWG hernia grades I and II, and hernia defects < 5cm. The study group was comprised of P4HB meshes; the comparator group was an aggregate of PP meshes. Clinical outcomes were assessed at 30 days.There was no significant difference in early wound morbidity, readmission, or reoperation between the P4HB and PP cohorts. A small number of patients experienced SSO, with ≤4% requiring procedural intervention. None of the patients (0% in all cases) experienced skin/soft tissue necrosis, infected seroma, infected hematoma, exposed/contaminated/infected mesh, enterocutaneous fistula, graft failure, or pain requiring intervention at 30-days. However, P4HB was associated with significantly greater operative time, length of stay, and use of myofascial release compared to PP (p<0.05 in all cases). Conclusions Short-term clinical outcomes associated with resorbable P4HB mesh are comparable to permanent synthetic PP mesh in umbilical and small to medium, routine ventral hernia repairs, despite significant differences in operative time and length of stay. Longer-term follow-up is needed to expand on the clinical relevance of these short-term findings.